Ultraviolet light–assisted electrokinetic conversion based on TiO2 electrodes. (December 2020) - Pei, Junxian; Song, Xianyin; Chu, Wenbin; Liu, Xiaowei; Deng, Wangquan; Cheng, Ting; Hu, Xuejiao; Yang, Peihua; Liu, Kang
Abstract: Fluidic nanogenerators have attracted increasing interests in applications of distributed electronics and self-powered systems. Here, we report a novel electrokinetic conversion device composed of an anodic aluminum oxide membrane, deionized water, and titanium oxide electrodes. Under ultraviolet light illumination, the electrokinetic device outputs stable and continuous short-circuit current without any electrode consumption or external circulation of ions. Based on the output behavior of the device at different pressures and light intensities, an interaction mechanism between the electrokinetic effects in nanochannels and ultraviolet light–induced radical recycle at the electrodes is proposed. The radical recycle process transfers charges between ions and electrons to achieve stable streaming current in electrokinetic systems, while streaming current induced positive and negative ions acumination facilities the radical recycle process. These results bring new insights into the charge transfer process in fluidic energy conversion devices and provide a new way to construct light-assisted microfluidic energy conversion systems. Graphical abstract: Image 1 Highlights: Electrokinetic nanogenerators with anodic aluminum oxide nanochannels, deionized water, and TiO2 electrodes are presented. The fluidic device output sustainable current under pressure-driven flow assisted by UV light. An interaction mechanism based on the electrokinetic effect and UV light–induced radical recycle is proposed.